Novel route for the synthesis of surfactant-assisted MoBi2(Se0.5Te0.5)5 thin films for solar cell applications. (25th February 2015) - Salunkhe, Manauti M.; Khot, Kishorkumar V.; Patil, Pramod S.; Bhave, Tejashree M.; Bhosale, Popatrao N.
Abstract : As-deposited thin film shows a fibrous reticulate framework, SDS-assisted synthesis produces a dendrite star fish like morphology, and TOPO-assisted synthesis produces nanothreads with flakes. Abstract : We have successfully synthesized MoBi2 (Se0.5 Te0.5 )5 thin films by using the self-organised arrested precipitation technique (APT) on ultrasonically cleaned glass and FTO-coated glass substrates. In the present investigation, we have synthesized MoBi2 (Se0.5 Te0.5 )5 thin films and studied the effects of the surfactants sodium dodecyl sulphate (SDS) and tri- n -octyl phosphine oxide (TOPO). The effects of the different surfactants on the opto-structural, morphological, compositional and electrical properties of the MoBi2 (Se0.5 Te0.5 )5 thin films were investigated by using UV-visible-NIR spectrophotometry, X-ray diffraction (XRD), scanning electron microscopy (SEM), atomic force microscopy (AFM), transmission electron microscopy (TEM), X-ray photoelectron spectroscopy (XPS), electrical conductivity (EC) and thermoelectric power (TEP) measurements. Optical study revealed that the as-deposited, SDS-assisted and TOPO-assisted thin films exhibited band gap energies of 1.46, 1.51 and 1.62 eV, respectively. XRD study confirmed that the surfactant-assisted thin films have broad and intense diffraction peaks compared to the as-synthesized thin film, indicating a more crystalline nature. SEM images confirmed that all the thin films are well adherent without containing any cracks, and that the different surfactants play a vital role in engineering of the surface morphology. The AFM study clearly showed that the surface roughness decreases for the surfactant-assisted thin films. The TEM and SAED patterns demonstrated that all samples are nanosized with porous surface morphology. The EDS and XPS measurements confirmed nearly stoichiometric thin film formation. The electrical study showed that all samples are semiconducting in nature with n-type conductivity. Finally these prepared electrodes were tested for their photoelectrochemical (PEC) performance in polysulphide electrolyte and promising results were obtained.